Control interno al área de compras y ventas y su incidencia en el rendimiento financiero del comisariato Mayte Andrea, cantón Valencia, año 2013 - Farez Peñaherrera, Mayte Andrea (2015)
The business world lives constant changes, due to this the implementation of new administrative trends, it is necessary to so it was curatorial Mayte Andrea research work, year 2013, aiming general the realization of Internal Control to the area of purchases and sales, and its incidence with financial performance to optimize its resources, through the same raised the following specific objectives: Analyze the current situation of drop Hummers and sales; Assess the internal control procedures that applied the company in the area of purchasing and sales; Measuring economic performance through financial indicators; Issue a report of internal controls using COSO I; books and documents on web pages were used in the theoretical framework, the legal framework is supported by laws, standards and regulations that served as support and support for the execution of the research work, in its development were used materials and methods that allowed its realization, similarly determined the type of research used in its development, established research techniques through which was to explain the problem, also created a fictitious auditing firm that allowed the development of the thesis. Through the interview with Head of Purchasing and Sales findings they met, with the result that the auditor faces an Acceptable Audit Risk 0.43% percentage obtained by assessing the inherent risk with 22% due to factors external threatening the company, risk Control with a risk level of 13.04% and a confidence level of 86.96% because of the findings following the evaluation of the components of the COSO I and risk Detection with 15% calculated on the basis of the experience of the auditor; measured the financial performance through its indicators allowing you to know the real situation of the company. Finally the conclusions, where the relevant circumstances of the investigation and the recommendations allowing possible solutions to problems are expressed are drafted.